Unleashing the potential of preprints: A new publishing model for a digital age - Pattinson, Damian (Septentrio Conference Series, 2021)
See RECORDING. The rise of preprints in the biomedical sciences has created new opportunities to transform how research is communicated and assessed. As researchers become more accustomed to posting their findings online as soon as they are ready to be shared, the delays that occur during peer review at journals become harder to countenance. If a finding is immediately made available as a preprint, why wait months for the journal version to be published? There is clearly still a need for the quality control that peer review provides, but it does not make sense to continue with the opaque systems that were designed for an age when findings were kept secret until they were published in a journal. In this talk I will discuss the ways in which eLife is working towards a new model to support the open review of preprints, while also developing technology that supports other experiments in this space.